Evaluasi Penyelenggaraan Diklat Penataan Ruang Daerah Angkatan I Tahun 2018 - Iswan Achmadi (Universitas Indraprasta PGRI Jakarta, 2022)
The evaluation of The Regional Spatial Planning Training for the 1st class of 2018 at BPSDM of DKI Jakarta Province is needed to inspect the effectiveness of this training, as the result of posttest and pretest shows that some participants have less satisfactory results, requiring them to take a remedial test in order to graduate from the training. Based on the background of the problem and to reach a more comprehensive result of research, evaluation is done to every component of training, which consists of context, input, process, and product of the training that is linked to the characteristic of participants. The study used a mixed of qualitative and quantitative method with descriptive approach and the CIPP evaluation model. The research result shows that: 1) The context component has been well-delivered, 2) The input component need to be more elevated, which includes the requirement of participants and provision of training facilities, 3) The process component has an excellent result, which includes the performance of training process with a score of 86,69, the curriculum implementation with a score of 83,75, training facilities usage with a score of 85,49, and trainer performance with score of 88,89, 4) The product component: all of participants are able to be graduated and the aspect to influence the level of graduating participants are their gender, age and work location.